The role of discipline "Olympic Education" in Training Specialists of "Physical Culture and Sport" in Kazakhstan - Bakhtiyarova, S.; Zhalel, Ali; Nurbagi, S.; Baitlessova, N.; Yergaliyev, A. (Cypriot Journal of Educational Sciences. - 2021, 2021)
Kazakhstan makes a significant contribution to the development of physical culture and sports in the Olympic games and as such, there is an urgent direction to study the prospects for the development of the educational services market and conduct research on consumers of educational services. The purpose of our study was to study and analyze the activities for the organization and implementation of work, related to the massive introduction of the ideas of Olympism and Olympic education in the daily life of both Kazakhstani specialists in the field of physical culture and sports, and the entire sports community. The study collected data through a survey involving 347 respondents working in the field of physical culture and sports in the Republic of Kazakhstan. Data was analyzed using percentages and content analysis. From the study, it was concluded that Olympic movement and Olympic education make the younger generation much smarter, more humane, more aesthetic and more tolerant. Казахстан вносит значительный вклад в развитие физической культуры и спорта на Олимпийских играх и в связи с этим существует актуальное направление изучения перспектив развития рынка образовательных услуг и проведения исследований потребителей образовательных услуг. Целью нашего исследования явилось изучение и анализ деятельности по организации и проведению работы, связанной с массовым внедрением идей олимпизма и олимпийского образования в повседневную жизнь как казахстанских специалистов в области физической культуры и спорта, и все спортивное сообщество. В исследовании собраны данные путем опроса 347 респондентов, работающих в сфере физической культуры и спорта в Республике Казахстан. Данные были проанализированы с использованием процентного и контент-анализа. Из исследования сделан вывод, что олимпийское движение и олимпийское образование делают подрастающее поколение намного умнее, человечнее, эстетичнее и толерантнее.
The role of discipline "Olympic Education" in Training Specialists of "Physical Culture and Sport" in Kazakhstan / S. Bakhtiyarova, Zhalel Ali, S. Nurbagi, N. Baitlessova, A. Yergaliyev. - Текст : непосредственный // Cypriot Journal of Educational Sciences. - 2021. - Vol. 16. Iss. 6. - Р. 3196-3212 . - ISSN 1305-9076
Keywords: импакт-фактор 2021; скопус; научный журнал; периодическое издание; дальнее зарубежье; зарубежное издание; спорт; олимпийское образование